Employing the Blue Ocean Strategy to Support the Digital Marketing Process in the Light of COVID-19 Pandemic - Abdel Aziz, Salwa Zaghloul Al-Borai (The Arab Journal of Administration, 2024)
The study aimed to present a proposal to develop marketing operations in light of measures of social distancing and home quarantine to guard against the repercussions of Covid-19, taking the blue ocean strategy to switch to digital marketing as a marketing method that has proven effective. The study found the following: The precautionary measures of Covid-19 have affected the capabilities of social and economic life, and therefore marketing, as a result of social distancing, home quarantine, decisions to restrict freedom of movement, and other precautionary measures. The means of digital transformation are considered an exit to support digital marketing for the purpose of bypassing the precautionary measures of Covid-19. That the dimensions of the proposed blue ocean strategy achieve the quality of digital marketing performance in light of the precautionary measures for Covid-19, and that accepting this hypothesis achieved great explanatory power that supports the application of this strategy for the purpose of overcoming the Covid-19 crisis. The proposed elements of the Blue Ocean strategy entail what is being increased on the current marketing situation for the purpose of shifting to digital marketing that supports the precautionary measures for Covid-19, and at the forefront of the arrangement is the necessity of including websites and electronic applications information on the cost of transportation and additional services that complement the purchases of a product or service. He accepts the hypothesis that the current situation of marketing does not achieve the quality of digital marketing performance in light of the Covid-19 measures, and this does not mean that there are shortcomings except as far as the precautionary measures taken by society as a result of the Covid-19 outbreak.